Prenatal Maternal Stress Causes Preterm Birth and Affects Neonatal Adaptive Immunity in Mice - Garcia-Flores, Valeria; Romero, Roberto; Furcron, Amy-Eunice; Levenson, Dustyn; Galaz, Jose; Zou, Chengrui; Hassan, Sonia S.; Hsu, Chaur-Dong; Olson, David; Metz, Gerlinde A. S.; Gomez-Lopez, Nardhy (Frontiers in Immunology, 2020)
Maternal stress is a well-established risk factor for preterm birth and has been associated with adverse neonatal outcomes in the first and subsequent generations, including increased susceptibility to disease and lasting immunological changes. However, a causal link between prenatal maternal stress and preterm birth, as well as compromised neonatal immunity, has yet to be established. To fill this gap in knowledge, we used a murine model of prenatal maternal stress across three generations and high-dimensional flow cytometry to evaluate neonatal adaptive immunity. We report that recurrent prenatal maternal stress induced preterm birth in the first and second filial generations and negatively impacts early neonatal growth. Strikingly, prenatal maternal stress induced a systematic reduction in T cells and B cells, the former including regulatory CD4+ T cells as well as IL-4- and IL-17A-producing T cells, in the second generation. Yet, neonatal adaptive immunity gained resilience against prenatal maternal stress by the third generation. We also show that the rate of prenatal maternal stress-induced preterm birth can be reduced upon cessation of stress, though neonatal growth impairments persisted. These findings provide evidence that prenatal maternal stress causes preterm birth and affects neonatal immunity across generations, adverse effects that can be ameliorated upon cessation.